First report of detection and molecular confirmation of Plasmodium ovale from severe malaria cases in central India. Issue 11 (4th September 2013) - Singh, R.; Jain, V.; Singh, P. P.; Bharti, P. K.; Thomas, T.; Basak, S.; Singh, N.
Abstract: Objective: We report for the first‐time detection of Plasmodium ovale in central India. Methods: From 2010, all hospitalised suspected malaria cases at the malaria clinic of the Regional Medical Research Centre for Tribals in Bastar district, central India, were screened. Plasmodium species were identified by microscopy and species‐specific nested PCR of 18s rRNA. Results: Of 256 enrolled cases of confirmed P. falciparum malaria by microscopy, P. ovale infection was detected in three cases (1.2%) by PCR and sequencing. Of these three cases, one had cerebral malaria and another had severe malaria anaemia. In both of these cases, P. ovale infection was mixed with P. falciparum, while in third case the infection was mixed with both P. falciparum and P. vivax . Phylogenetic analysis revealed that these isolates showed closed homology with West African genotypes. Conclusion: All three hospitalised patients were originally residents of remote inaccessible forest villages and never moved out of their residence. This finding also has implications in malaria control and elimination as P. ovale causes relapses. This study highlights the need of molecular diagnosis of malaria species for appropriate treatment and control.